Load shifting impact on generating adequacy assessment during peak period - Alsaedi, Malik Abdulrazzaq; Jabir, Hussein Jumma; Albaker, Baraa Munqith (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The load shifting technique is widely implemented in electrical power generation due to its considerable impact on system reliability. The evaluation of load shifting benefits towards the adequacy of generation systems requires an accurate assessment. If the generation unit’s capacity is insufficient to meet the system load, then assistance is required from alternative sources. Load shifting, as a primary demand-side management technique, is used efficiently in electrical power networks given that the energy clipped/curtailed owing to load curtailment and peak clipping can be recovered during the off-peak period. The reliability of a generic framework for the prospective integration of a load shifting technique, with preventative and corrective actions as alternatives to peaking units, is investigated in this study. The optimal rate of load shifting in terms of expected energy not supplied is also investigated. Results show that preventive load shifting (PLS) can act as peaking units when the total generated capacity is within specific limits. Meanwhile, corrective load shifting can act as a better alternative than PLS and peaking units. To calculate expected energy not supplied, sequential Monte Carlo simulation is utilized. This study is conducted using the IEEE reliability test system.